Penerapan Model Pembelajaran Kooperatif Tipe Team Games Tournament Berbantuan Media Powtoon untuk Meningkatkan Hasil Belajar Peserta Didik - Brata Susena Atmaja Prasetya; Harini Harini; Mintasih Indriayu (Journal on Education, 2024)
The objective of this research is to determine: 1) the influence of implementing the cooperative learning model Teams Games Tournament (TGT) assisted by Powtoon media in improving students' learning outcomes; 2) the difference in the effectiveness of applying the TGT learning model assisted by Powtoon compared to the conventional teaching model in enhancing students' learning outcomes. This study employs a quantitative research approach with an experimental method. The sampling technique used is cluster sampling. Hypothesis testing in this research involves independent sample t-tests and N-Gain tests. The results of this study indicate that: 1) there is a difference in learning outcomes between the control and experimental groups, as evidenced by the calculated t-value of 5.830 > the critical t-value of 1.994; 2) there is a difference in the effectiveness of applying the cooperative learning model Teams Games Tournament compared to the conventional teaching model, with N-Gain scores of 76.73% for the TGT learning model and 46.17% for the conventional learning model. The t-test on N-Gain scores indicates a significance value of 0.000 < 0.05. Thus, it can be concluded that the application of TGT assisted by Powtoon is effective in improving students' learning outcomes compared to conventional teaching methods.